The Role of the Communicative Approach in ELT - Mashhura Hakimova; Nozima Sayfiddinova (Genius Journals, 2022)
The aim of the communicative approach in teaching foreign languages (Communicative language teaching) is developing students' semantic perception and understanding of foreign speech, as well as mastering the language material for constructing speech utterances. This article discusses the use of communicative situations to successfully master English as a foreign language so that students must know not only linguistic forms, but also be able to use them for real communication.
Keywords: Communicative Approach; Competence; Speaking Activities